Grapefruit juice effects - Bita Mesgarpour; Hamidreza Adhami; Masoud Amanlou (Institue of Medicinal Plants, ACECR, 2002)
Grapefruit juice is used as a nutritional supplement for potassium loss. Grapefruit pectin can reduce cholesterol and promote regression of atherosclerosis. Other effects include induction of red cell aggregation, reduction of hematocrits and possible anti-cancer effects. One glass of grapefruit juice or half of a grapefruit can significantly increase the absorption as well as decrease the metabolism (inactivation) of many commonly used oral medications. The interaction between some drugs and grapefruit juice is called the "grapefruit juice effect". The result is that greater amounts of the affected drugs enter the bloodstream, and these drugs can have increased therapeutic effects or increased toxicity. The mechanism of the grapefruit juice effect is probably that one or more of the chemicals (most likely bioflavonoids and/or furanocoumarins) in grapefruit juice inhibit the cytochrome P450 isoenzymes, especially 3A4 isoenzyme. Hence, any drug normally metabolized by that enzyme may show increased effectiveness and/or toxicity when taken with grapefruit juice. This review discusses about clinical trials of drugs that their effects are potentiated by grapefruit juice include some antihistamines, benzodiazepines, calcium channel blockers. cholesterol lowering statins, immunosuppressants and others.